Completely ossified thoracic intradural meningioma in an elderly patient: A case report and literature review. Issue 25 (19th June 2020) - Xu, Feng; Tian, Zhisen; Qu, Zhigang; Yao, Liyu; Zou, Congcong; Han, Wanrong; Zhang, Caihong; Fu, Changfeng; Wang, Yuanyi
Abstract: Rationale: Spinal meningioma is the second most common spinal neoplasm that commonly occurs in middle-aged women. As a rare histological variation of meningioma, completely ossified meningioma (OSM) and its standard surgical strategies have been reported. However, the surgical outcomes of elderly OSM cases (age >70) are less investigated. Herein, we intend to present an elderly OSM case and review the elderly OSM cases in published literatures. Patient concerns: An 85-year-old female presented with 10-year history of back pain and developed radiating pain on her left lower extremity within the last 2 weeks. Diagnoses: A magnetic resonance imaging scan revealed an intradural tumor at the T11 level. A computed tomography scan demonstrated that the mass was completely ossified and had distinct borders (Fig. 1 D–F). In a dynamic contrast-enhanced magnetic resonance imaging scan, the mass presented as a lateral intradural extramedullary tumor with abundant blood supply (Fig. 2 ). Interventions: The patient underwent en bloc intradural tumorectomy via posterior approach. Outcomes: After surgery, the patient's pain was relieved. However, the patient spent another 3 weeks in hospital due to a series of post-surgery complications, including hypostatic pneumonia, pulmonary heart failure, hydrothorax in both thoracic cavities, hypoproteinemia, and deep venous thrombosis on both of her legs. The complications recovered after 3-weeks treatment. In 1-year follow up, no additional symptom was found and the patient was recurrence free. Lessons: Our report indicated that the surgical outcome can be satisfying in elderly OSM patients, while the post-operative complications frequently occur due to the poor physical condition of elderly patients. As a result, treatment of peri-operative complications of elderly OSM patients also deserves greater attention along with surgical resection.